Implementation of Learning Model Start with a Question (LSQ) to Improve Activeness and Students’ Learning Result - Wahyuningsih, Roy; Huda, Ahmad Fatkurohman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to increase student activity and learning outcomes by applying the Learning Start with A Question (LSQ) learning strategy. This research is a classroom action research conducted in 2 cycles. The subjects of this study were the fifth grade students of SDN Pinggir Nganjuk Regency, totaling 40 odd semester students for the 2020/2021 academic year. The instruments used in this study were the teacher's activity or performance observation sheet, student activity observation sheet and test sheet. Data collection techniques usedwere observation, documentation and tests. The results of the study indicate that the Learning Start with A Question (LSQ) learning model could increase the activity of fifth grade students at SDN Pinggir Nganjuk Regency. This increase could be seen from the increase in the percentage of student activity that could be seen from the average percentage in the first cycle of students reaching 66.95%, while in the second cycle there was an increase of 93.78%. Meanwhile, in the first cycle, the increase in student learning outcomes with a percentage of 51.22%, in the second cycle there was a very good increase again with a percentage of 92.68%. Based on the results of tests that have been carried out on social studies subject matter, it is known that there has been an increase in student learning outcomes.